Insect pollinators of conference pear (Pyrus communis L.) and their contribution to fruit quality - Fountain, Michelle T; Mateos-Fierro, Zeus; Shaw, Bethan; Brain, Phil; Delgado, Alvaro (Journal of Pollination Ecology, 2019)
The pear (Pyrus communis L.) cultivar, Conference, is parthenocarpic but misshapes and marketable fruit losses of 6% at harvest are common. In other studies, insect flower visitors are identified as important for apple quality, but far fewer studies have examined the effects of insects and cross-pollination on pear quality. Using a range of replicated field experiments, this project aimed to determine the; 1) biodiversity of pear blossom insect visitors, 2) pollen limitation and fruit quality as a function of distance from the orchard edge and number of insect visitors, and 3) importance of cross pollination on fruit quality. A wide range of insects, >30 species, visited pear flowers including honey bees, bumble bees, solitary bees and hoverflies. Honey bees were the most frequent visitors, but all guilds, to a greater or lesser extent, made contact with the reproductive parts of the flower. Insect visits resulted in 10% higher fruit set. There was no effect of distance from the edge (up to 50 m) of orchard on the quality of pears, and no consistent difference in the guild of insects visiting at distances from the orchard boundary. Cross-pollination with the variety Concorde produced better quality Conference fruits. We discuss how pollination of Conference pears could be managed to improve yields of marketable fruit.